2008
DOI: 10.1016/j.cvsm.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Canine Influenza

Abstract: In 2004, the isolation of an influenza virus from racing greyhounds changed the point of reference for discussions about influenza virus in dogs. A virus isolated from greyhounds did not have its origin in a previously described human influenza virus but came from a virus with an equine history. More significantly, evidence emerged to indicate that the virus was capable of transmission from dog to dog. This virus is now referred to as canine influenza virus (CIV) and is the focus of this review. Because the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
86
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 12 publications
3
86
0
1
Order By: Relevance
“…Detection of CIV is frequently attempted by traditional virus isolation (VI) in embryonated hens' eggs or in Madin-Darby canine kidney (MDCK) cells. 4 There have been some conflicting reports over the sensitivity of antigen-capture enzyme-linked immunosorbent assays for the detection of CIV in dogs. 4,15 Presence of CIV nucleic acid in clinical specimens has been confirmed by traditional reverse transcription polymerase chain reaction (RT-PCR) and real-time RT-PCR assays targeting the matrix (M) gene of Avian influenza virus or by an real-time RT-PCR assay specific for the H3 HA or the M gene of CIV.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Detection of CIV is frequently attempted by traditional virus isolation (VI) in embryonated hens' eggs or in Madin-Darby canine kidney (MDCK) cells. 4 There have been some conflicting reports over the sensitivity of antigen-capture enzyme-linked immunosorbent assays for the detection of CIV in dogs. 4,15 Presence of CIV nucleic acid in clinical specimens has been confirmed by traditional reverse transcription polymerase chain reaction (RT-PCR) and real-time RT-PCR assays targeting the matrix (M) gene of Avian influenza virus or by an real-time RT-PCR assay specific for the H3 HA or the M gene of CIV.…”
mentioning
confidence: 99%
“…2,4 Sequence analysis of Canine influenza virus (CIV) from the original outbreak (A/canine/FL/43/04) revealed that 8 gene segments of this virus shared $96% nucleotide sequence homology with that of the H3N8 EIV subtype, suggesting that CIV resulted from direct interspecies transmission of EIV to dogs without genetic reassortment. 2,11 The sequence changes in the hemagglutinin gene (H3 HA) are indicative of adaptive evolution of the virus in its new host.…”
mentioning
confidence: 99%
See 3 more Smart Citations